IMPLEMENTASI PEMBELAJARAN PARTISIPATIF MELALUI FOCUS GROUP DISCUSSION DALAM MENINGKATKAN KEMAMPUAN KOMUNIKASI MAHASISWA - Ahmad Muslim (Jurnal Paedagogy, 2017)
Participatory Learning is a learning activity that emphasizes that students have learning needs, understand learning techniques and learning behavior that can lead to educational interactions between students and students and students and educators. The element of learning activities is characterized by a deliberate, planned and systematic effort made by educators to empower the existing potentials possessed by students. Participatory learning is defined as an effort by educators to include students in learning activities, namely in the stages of program planning, program implementation and program assessment. Participatory learning with this concept reflects the implementation of learning that is democratic, wise, conducive, flexible and seeks to empower the potential of each student. Participatory Learning developed through Focus Group Discussions is directed at improving student communication skills. This learning is carried out by forming student study groups who are accompanied by educators (lecturers) in carrying out their learning activities. The strategy for implementing participatory learning through focus group discussions, namely by involving all members of the study group in the learning program planning process, the learning implementation process and learning assessment / evaluation. Learning is carried out by carrying out communication exercises both in class and outside the classroom which are adjusted to the learning activity plans compiled with discussion group members. Through the exercises that are carried out, of course, it will be able to improve student communication skills which can be implemented in the learning process of learning as well as in the broader application process.